Promene maksimalne snage kod fleksora zgloba lakta posle šest nedeljnog vežbanja sa skraćenim amplitudama - Vuksanovikj, Vladimir; Jovanovski, Jovan (Crnogorska sportska akademija, 2010)
17 participants were put under longitudinal program for 6 weeks, which program should influence the maximal power potential within the flexor muscle of the elbow. Test were given for one maximal repetition, anthropometrical measures as well as test for angular speed. The participant were under test before the beginning of the 6 weeks program (initial testing) and then after the ending of the program (final testing). During the six weeks program the participants had a task to do power exercises on the Scot’s bench, with the individual weight, in the range of semiflexion until maximal flexion of the elbow joint and vice versa (modified amplitude of the movements). The analyses and result from the statistical operation have shown positive changes at the participant’s maximal power (15,27%) also at the tested angular speed (96,72%). The rest of the tests have shown some objective changes which were not statistically significant. The analysis’s and conclusion are in favor of the program for transformation of motorics capabilities and they are directly focused of modification of power component.
Keywords: exercising; maximal force; amplitude; elbow joint; shortened (modified) amplitude; repetition; semiflexion; angle speed; anthropometry; longitudinal